CURRENT TRENDS IN THE PRACTICE OF LABORATORY MEDICINE. - Emilia P. Georgieva; Galina R. Petrova; Todorka I. Kostadinova; Stanislava Pavlova (Peytchinski Publishing, 2015)
The paper present the perspectives and the possible benefits of the POCT tests, conducted outside of the clinical laboratories. Laboratory tests are objective in their character, which is one of the main reasons for the constant increase in the number of laboratory tests. The fast development of the technology in clinical laboratories, leads to the constant introduction of new markers, as well as the methods and equipment for the establishment of their values. Moving the laboratory diagnostics closer to the patient's location (point of care testing) is a new tendency in the policy of health care. The tendency may be applied and is expanding, because of the fast development of biotechnologies. In a worldwide scale, POCT is essential for the public health care.